2020
DOI: 10.1101/2020.01.26.919985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA expression profiling of ACE2, the receptor of SARS-CoV-2

Abstract: A novel coronavirus (2019-nCov) was identified in Wuhan, Hubei Province, China in December of 2019. This new coronavirus has resulted in thousands of cases of lethal disease in China, with additional patients being identified in a rapidly growing number internationally. 2019-nCov was reported to share the same receptor, Angiotensin-converting enzyme 2 (ACE2), with SARS-Cov.Here based on the public database and the state-of-the-art single-cell RNA-

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
888
3
39

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 921 publications
(1,008 citation statements)
references
References 23 publications
53
888
3
39
Order By: Relevance
“…The worldwide ongoing trials, including those involving the care of patients in our institute [90], will verify whether the hopes raised by chloroquine in the treatment of COVID-19 can be confirmed. expressed on pneumocytes [85,99]. Binding to ACE2 is expected to trigger conformational changes in the S glycoprotein allowing cleavage by the transmembrane protease TMPRSS2 of the S protein and the release of S fragments into the cellular supernatant that inhibit virus neutralisation by antibodies [100].…”
Section: Resultsmentioning
confidence: 99%
“…The worldwide ongoing trials, including those involving the care of patients in our institute [90], will verify whether the hopes raised by chloroquine in the treatment of COVID-19 can be confirmed. expressed on pneumocytes [85,99]. Binding to ACE2 is expected to trigger conformational changes in the S glycoprotein allowing cleavage by the transmembrane protease TMPRSS2 of the S protein and the release of S fragments into the cellular supernatant that inhibit virus neutralisation by antibodies [100].…”
Section: Resultsmentioning
confidence: 99%
“…One reason is that the vast surface area of the lung makes the lung highly susceptible to inhaled viruses, but there is also a biological factor. Using normal lung tissue from eight adult donors, Zhao et al [14] demonstrated that 83% of ACE2-expressing cells were alveolar epithelial type II cells (AECII), suggesting that these cells can serve as a reservoir for viral invasion. In addition, gene ontology enrichment analysis showed that the ACE2-expressing AECII have high levels of multiple viral process-related genes, including regulatory genes for viral processes, viral life cycle, viral assembly, and viral genome replication [14], suggesting that the ACE2-expressing AECII facilitate coronaviral replication in the lung.…”
Section: Enrichment Distribution Of Ace2 Receptor In Human Alveolar Ementioning
confidence: 99%
“…Recent reports of the ACE2 expression analysis in lung tissues from Asian and Caucasian populations are still controversial. The single-cell RNA-seq analysis reported that the Asian donor had much higher ACE2 expression cell ratio than white and African-American donors 6 . In contrast, the ACE2 expression analysis using the RNA-seq and microarray datasets from control lung tissues indicated there were no significant differences between Asian and Caucasian, or male and female 11 .…”
Section: © the Author(s) 2020mentioning
confidence: 99%
“…In contrast, the ACE2 expression analysis using the RNA-seq and microarray datasets from control lung tissues indicated there were no significant differences between Asian and Caucasian, or male and female 11 . The ACE2expressing cells are a very small part of cells in lung tissues 6 . The sample size and the purity of ACE2-positive cells in the selected samples would influence the conclusions.…”
Section: © the Author(s) 2020mentioning
confidence: 99%